The Comparation of Sport Massage and Hydrotherapy Cold Water to Physiological Recovery - Hawin Fahmi; Kunjung Ashadi (STKIP Muhammadiyah Kuningan, 2019)
The purpose of this study was to show a comparison of recovery sport massage methods and cold water hydrotherapy to the physiological recovery of decreased lactic acid levels and pulses using a purposive sampling technique. This research method is quantitative research with a descriptive approach. The subjects of this study were 16 Wushu Sanda KONI athletes in Blitar District which were divided into two groups. For data analysis using the mean, standard deviation and pair t test and unpair t test. Based on the results of this study indicate that there are significant differences for the comparison of the decrease in lactic acid levels between the use of recovery sport massage methods and cold water hydrotherapy, with calculations that show a value of P <0.05 where the average value of lactic acid levels decreases recovery sport massage 4.92 nMol / L and cold water hydrotherapy of 3.91 nMol / L. Whereas the decrease in pulse ratio showed that there was no significant difference between the use of recovery sport massage and cold water hydrotherapy methods, with calculations that showed P> 0.05 where the average pulse rate recovery sport massage method was 8.35 Beat Per Minute and hydrotherapy cold water 77.5 Beat Per Minute